Transplantasi Organ Tubuh Sebagai Metode Pengobatan Dalam Pandangan Hukum Islam Kontemporer: Organ Transplantation As A Medical Treatment In The Perspective Of Contemporary Islamic Law - Sabubu, Theo Alif Wahyu (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
This study aim to examine the legal status of organ transplantation from the perspective of contemporary Islamic Law, including donations from living donors, deceased donors, and non-Muslim donors, as well as to identify the ethical, legal, and medical principles that govern its permissibility. The research employs a library-based method with a normative-theological approach by reviewing classical Islamic jurisprudence, contemporary scholarly opinions, resulotions of international fiqh bodies, and relevent fatwas issued by the Indonesian Council of Ulama (MUI). The findings show that most contemporary scholars permit organ transplantation based on the principles of maqasid al-shari’ah, particularly the preservation of life (hifz al-nafs), provided that the procedure does not cause significant harm to the donor, is supported by valid consent, and is free from any commercial elements. Transplantation from deceased donors is likewise deemed permissible under conditions of necessity and with due respect for the dignity of the corpse. Additionally, the use of organs from non-Muslim donors is allowed since organs do not possess religious identity. In conclusion, organ transplantation is acceptable within Islamic law as long as it complies with established shar’i principles, ethical medical standards, and regulatory requirements, and aligns with the overarching objective of preserving human life.